\(\left(x^2+x+1\right)\left(x^2-x+1\right)\left(x^4-x^2+1\right)\left(x^8-x^4+1\...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

18 tháng 7 2022

\(\left(x^2+x+1\right)\left(x^2-x+1\right)\left(x^4-x^2+1\right)\left(x^8-x^4+1\right)\\ =\left[\left(x^2+1\right)^2-x^2\right]\left(x^4-x^2+1\right)\left(x^8-x^4+1\right)\\ =\left(x^4+x^2+1\right)\left(x^4-x^2+1\right)\left(x^8-x^4+1\right)\\ =\left[\left(x^4+1\right)^2-x^4\right]\left(x^8-x^4+1\right)\\ =\left(x^8+x^4+1\right)\left(x^8-x^4+1\right)\\ =\left(x^8+1\right)^2-x^8\\ =x^{16}+x^8+1\)

30 tháng 5 2017

a) 3(22+1)(24+1)(28+1)(216+1)

=(2+1)(2-1)(22+1)(24+1)(28+1)(216+1)

=(22-1)(22+1)(24+1)(28+1)(216+1)

=(24-1)(24+1)(28+1)(216+1)

.......

=(216-1)(216+1)=232-1

13 tháng 10 2019

a) \(\left(x+2\right)\left(x-2\right)-\left(x-3\right)\left(x+1\right)\)

\(=x^2-4-\left(x^2+x-3x-3\right)\)

\(=x^2-4-x^2-x+3x+3\)

\(=2x-1\)

b) \(3\left(2^2+1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)

\(=\left(2^2-1\right)\left(2^2+1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)

\(=\left(2^4-1\right)\left(2^4+1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)

\(=\left(2^8-1\right)\left(2^8+1\right)\left(2^{16}+1\right)\)

\(=\left(2^{16}-1\right)\left(2^{16}+1\right)=2^{32}-1\)

27 tháng 4 2017

a)\(x\left(2x^2-3\right)-x^2\left(5x+1\right)+x^2\)

=\(2x^3-3x-5x^3-x^2+x^2=-3x^3-3x\)

b) \(3x\left(x-2\right)-5x\left(1-x\right)-8\left(x^2-3\right)\)

\(=3x^2-6x-5x+5x^2-8x^2+24=-11x+24\)

c) \(\dfrac{1}{2}x^2\left(6x-3\right)-x\left(x^2+\dfrac{1}{2}\right)+\dfrac{1}{2}\left(x+4\right)\)

\(=3x^3-\dfrac{3}{2}x^2-x^3-\dfrac{1}{2}x+\dfrac{1}{2}x+2=2x^3-\dfrac{3}{2}x^2+2\)

14 tháng 1 2016

-x^61+5*x^60+x^59-5*x^58-x^55+5*x^54+x^53-5*x^52-x^49+5*x^48+x^47-5*x^46x^43+5*x^42+x^41-5*x^40-x^37+5*x^36+x^35-5*x^34-x^49+5*x^48+x^47-5*x^46x^43+5*x^42+x^41-5*x^40-x^37+5*x^36+x^35-5*x^34-x^31+5*x^30+x^27-5*x^26-x^25+5*x^24+x^21-5*x^20-x^19+5*x^18+x^15-5*x^14-x^13+5*x^12+x^9-5*x^8-x^7+5*x^6+x^3-5*x^2-x+5

17 tháng 6 2018

a/ \(\left(x+3\right)^2-\left(x-2\right)\left(x+2\right)\)

\(\left(x+3\right)^2-\left(x^2-4\right)\)

\(\left(x+3\right)^2-x^2+4\)

\(\left(x+3-2\right)\left(x+3+2\right)+4\)

\(4+\left(x+1\right)\left(x+5\right)\)

b/ \(\left(3x-4\right)^2-\left(x-4\right)\left(x+4\right)-8x^2\)

\(\left(3x-4\right)^2-\left(x^2-16\right)-8x^2\)

\(\left(3x-4\right)^2-x^2+16-8x^2\)

\(\left(3x-4\right)^2-9x^2+16\)

\(\left(3x-4-3x\right)\left(3x-4+3x\right)+16\)

\(-4\left(6x-4\right)+16\)

\(4\left(4-6x\right)+16\)

\(4\left(4-6x+1\right)\)

\(4\left(5-6x\right)\)

c/ \(\left(x-2\right)\left(x+2\right)+\left(x-3\right)\left(x+3\right)-x\left(2x+1\right)-4\)

\(x^2-4+x^2-9-2x^2-x-4\)

\(-17-x\)

\(-\left(17+x\right)\)

27 tháng 6 2016

a) \(x\left(x^2-16\right)-\left(x^2+1\right)\left(x-1\right)\) =\(x^3-16x^2-x^3+x^2-x+1\)

                                                        = \(x^2-17x+1\)

b) \(\left(y^2-9\right)\left(y^2+9\right)-\left(y^4-4\right)\) = \(\left(y^4-81\right)-\left(y^4-16\right)\)

                                                       =\(-65\)

27 tháng 6 2016

bạn tính sai câu a